Use of geoprópolis on quail egg quality - Silva, Áurea dos Santos; Correa , Elen Cristina Pimentel; Mota , Iris Mayara Leão; Santos , Camilly Maria Santos dos; Ferreira , Layza Beatriz Barroso; Santos, Graciene Conceição dos (Revista de Ciências Agroveterinárias, 2024)
Egg is a highly nutritious food rich in proteins and vitamins but as all products of animal origin the egg loses quality quickly in the absence of appropriate methods of conservation, in this sense, an experiment was conducted with the objective of evaluating the quality of quail eggs not refrigerated, submitted to the surface treatment of the shell using geoprópolis solution of the species Melipona interrupta. The quality parameters analyzed were: weight loss; specific gravity; pH of the yolk and pH of the albumen. Analysis of variance was performed using a model including the effects of surface treatment of the bark, storage time, and interaction between these factors. As there was no interaction between treatments and storage time, the mean surface treatment of the eggshell was compared by the T test at 5% probability and the mean effects of storage time were compared by the SNK test (Student Newman-Keuls) at a 5% probability. With the increase of storage time, the eggs presented reduction in specific gravity and increase in weight loss, pH of the yolk and pH of the albumen, regardless of whether they received the surface treatment in the shell. The surface coating of quail eggshells with 10% geopropolis solution is not effective in maintaining the internal quality of eggs over 55 days of storage.